Informal teaching and learning of English in secondary schools: EFL students’ perspectives - Junining, Esti; Muttaqin, Syariful; Khasanah, Ismatul; Worobroto, Purwaningrum Elisabeth (CV. Yudhistt Fateeh, 2026)
As Indonesia becomes increasingly integrated into the global economy, English proficiency is essential for both educational and professional opportunities. However, traditional classroom instruction often prioritizes grammar and writing, resulting in limited development of students' speaking and listening skills. This study investigates students’ perceptions of informal English learning through their participation in the English Club at SMPN 14 Malang. Informal learning environments offer a dynamic setting for practicing English through discussions, storytelling, and interactive activities, thereby fostering both confidence and fluency. Employing a qualitative descriptive approach, the study gathered data from 20 students using open-ended questionnaires to explore their experiences. The findings reveal that students value the club’s relaxed atmosphere, interactive learning methods, and social elements, all of which contribute to increased motivation and language acquisition. Nevertheless, some students report difficulties with public speaking, group dynamics, and the pacing of activities. Recommendations for improvement include incorporating more film-based sessions and maintaining a fun, low-pressure learning environment. This study underscores the role of informal learning in complementing formal instruction and provides insights for educators seeking to design more engaging English language experiences.